2022
DOI: 10.1242/jeb.243414
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of prenatal glucocorticoids and thyroid hormones on developmental plasticity of mitochondrial aerobic metabolism, growth and survival: an experimental test in wild great tits

Abstract: Developmental plasticity is partly mediated by transgenerational effects, including those mediated by the maternal endocrine system. Glucocorticoid and thyroid hormones may play central roles in developmental programming through their action on metabolism and growth. However, the mechanisms by which they affect growth and development remain understudied. One hypothesis is that maternal hormones directly affect the production and availability of energy-carrying molecules (e.g. ATP) by their action on mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 82 publications
3
36
0
Order By: Relevance
“…The latter results are not fully surprising considering the limited evidence supporting a prenatal programming of plasma THs (sex-specific effect on T4 only, Hsu et al 2017;no effect, Hsu et al 2020) or mitochondrial density (no effect, Hsu et al 2020). Yet, our measurements are limited to blood and tissue-specific effects of TH on mitochondrial density or TH-related cellular machinery (receptors and converting enzymes; Ruuskanen et al 2022) may occur as this has been shown for instance for glucocorticoids (Weber et al 2002). According to the metabolic telomere attrition hypothesis, telomere shortening is likely to be increased during energy-demanding periods, and accelerated growth under limited resources is likely carrying a metabolic cost (Casagrande and Hau, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The latter results are not fully surprising considering the limited evidence supporting a prenatal programming of plasma THs (sex-specific effect on T4 only, Hsu et al 2017;no effect, Hsu et al 2020) or mitochondrial density (no effect, Hsu et al 2020). Yet, our measurements are limited to blood and tissue-specific effects of TH on mitochondrial density or TH-related cellular machinery (receptors and converting enzymes; Ruuskanen et al 2022) may occur as this has been shown for instance for glucocorticoids (Weber et al 2002). According to the metabolic telomere attrition hypothesis, telomere shortening is likely to be increased during energy-demanding periods, and accelerated growth under limited resources is likely carrying a metabolic cost (Casagrande and Hau, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with a direct elevation of yolk THs in altricial pigeons and precocial quail, incubation duration was not extended (Hsu et al, 2017; Sarraude et al, 2020b). In fact, experimentally elevated yolk THs might even shorten incubation duration (in great tits, Cossin‐Sevrin et al, 2022). In a reptile species (short‐necked turtles Emydura macquarii ), exogenously injected T3 in the middle of incubation was also found to shorten incubation duration (McGlashan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In experiments with a direct elevation of yolk THs in altricial pigeons and precocial quail, incubation duration was not extended (Hsu et al, 2017;Sarraude et al, 2020b). In fact, experimentally elevated yolk THs might even shorten incubation duration (in great tits, Cossin-Sevrin et al, 2022).…”
Section: Does Precocial Development Require More Maternal Ths?mentioning
confidence: 98%
“…Thyroid hormones are important for a number of developmental processes in birds during hatching and nestling development ( De Groef et al, 2013 ). A number of recent studies examined the influence of maternal thyroid hormones passed on in the egg on subsequent development in altricial species development ( Hsu et al, 2020 ; Sarraude et al, 2020 ; Cossin-Sevrin et al, 2022 ). Elevating egg yolk thyroid hormones resulted in earlier hatching and larger hatchlings in collared flycatchers ( Ficedula albicollis ) ( Hsu et al, 2019 ) but had no effect in the great tit hatchling ( Parus major ) ( Cossin-Sevrin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies examined the influence of maternal thyroid hormones passed on in the egg on subsequent development in altricial species development ( Hsu et al, 2020 ; Sarraude et al, 2020 ; Cossin-Sevrin et al, 2022 ). Elevating egg yolk thyroid hormones resulted in earlier hatching and larger hatchlings in collared flycatchers ( Ficedula albicollis ) ( Hsu et al, 2019 ) but had no effect in the great tit hatchling ( Parus major ) ( Cossin-Sevrin et al, 2022 ). The effect on the collared flycatcher disappeared quickly in the developing nestling.…”
Section: Introductionmentioning
confidence: 99%